Ruang Cyberfeminism di Balik Media Sosial Instagram Jakarta Feminist - Yuni Lasari (Jurnal Komunikasi Nusantara, 2023)
The presence of social media as a home for activists and social movements explains that public spaces today can spread into virtual spaces and have the same function as conventional public spaces. Through the @Jakartafeminist Instagram account, Jakarta Feminist builds a new, safe public space for women to speak up about their conditions. Using Habermas's theory of public space and netnographic research method, the research subject is selected by adopting six stages carried out by Kozinet that also accompanied the researcher's experience in the field. The research was conducted from July 2021 to April 2022, starting with observations and recording field notes daily, making reflections, documenting activities, conducting interviews, and analyzing them. The results show that the social movement carried out by Jakarta Feminist provides options for the presence of a safe public cyberspace and can help reduce gender bias. The choice of Instagram as a tool for daily activities from Jakarta Feminist is adjusted to the segmentation they reach, the young people, and to make it easier for the team to provide information visually to followers. Jakarta Feminist's Instagram social media is a promotional medium for disseminating feminist perspectives shown in programs, classes, and campaigns made in cyberspace. The topics and themes are related to Patriarchal culture and domestic violence cases, KBGO and the importance of privacy, consent, feminist ideology, myths about feminism, coalitions, and socialization between organizations, RUU PKS, and intersectionality issues. The cyberfeminist space built in this commentary sparked a critical sense for everyone who finished reading the caption. Abstrak Kehadiran media sosial sebagai rumah bagi para aktivis dan gerakan sosial menjelaskan bahwa ruang publik saat ini dapat menggunakan ruang virtual. Melalui media sosial instagram @Jakartafeminist, Jakarta Feminist membangun sebuah ruang publik baru yang aman bagi perempuan untuk speak up akan kondisi yang dialaminya. Dengan menggunakan teori ruang publik Habermas dan metode penelitian netnografi, subjek penelitian dipilih dengan mengadopsi enam tahapan Kozinet di mulai sejak Juli 2021-April 2022 yakni pengamatan dan mencatat fieldnote setiap hari, membuat refleksi, mendokumentasikan kegiatan, melakukan wawancara hingga menganalisanya. Hasil penelitian menunjukkan bahwa gerakan sosial yang dilakukan oleh Jakarta Feminist memberikan opsi hadirnya ruang publik cyber yang aman dan mampu membantu mengurangi bias gender. Pemilihan Instagram sebagai alat dalam melakukan aktivisme disesuaikan dengan segmentasi audiens yakni anak muda milenial. Media sosial Instagram Jakarta Feminist hadir sebagai media promosi penyebarluasan perspektif feminis ditunjukkan dalam program, kelas dan kampanye yang dibuat di ruang cyber berkaitan dengan topik diantaranya melepaskan diri dari belenggu budaya Patriarki dan Kasus KDRT, KBGO dan pentingnya privasi, isu interseksionalitas, pentingnya consent, ideologi feminisme, mitos soal feminisme, koalisi dan sosialisasi antar organisasi, RUU PKS, serta isu interseksionalitas. Ruang cyberfeminism yang dibangun memantik rasa kritis untuk setiap orang yang mengikuti aktivitasnya.